Objective predictors of 'early tolerance' to ventral intermediate nucleus of thalamus deep brain stimulation in essential tremor patients. Issue 8 (August 2018) - Merchant, Shabbir Hussain; Kuo, Sheng-Han; Qiping, Yu; Winfield, Linda; McKhann, Guy; Sheth, Sameer; Pullman, Seth L.; Ford, Blair
Highlights: Spiral analysis identified differences in ET patients developing tolerance to DBS. Potential tolerance to Vim DBS in ET can be predicted pre-operatively. Objective kinematic testing can aid in pre-operative assessment of complex tremors. Abstract: Objective: To identify pre-operative clinical and computerized spiral analysis characteristics that may help ascertain which patients with Essential Tremor (ET) will exhibit 'early tolerance' to ventral intermediate nucleus of thalamus (Vim) deep brain stimulation (DBS). Methods: Identification of comparative characteristics of defined cases of 'early tolerance' versus patients with sustained satisfactory response treated with Vim DBS surgery for medically-refractory ET, based on retrospective chart review by a clinician blinded to the findings of computerized spiral analysis. Results: Statistically significant differences in two spiral analysis indices, SWVI and DoS, were found in the dominant upper limbs of patients who developed 'early tolerance', whereas the clinical characteristics were not significantly different. Conclusion: Objective measurements of upper limb kinematics using graphonomic tests like spiral analysis should be considered in the pre-operative evaluation for DBS, especially in the setting of moderate-severe predominantly action and proximal postural tremors. Significance: Ours is the first investigation looking into the pre-operative clinical and objective physiologic characteristics of the patients who develop 'early tolerance' to Vim DBS for the treatment of essential tremor. The study has significant implications for pre-operative evaluation and potential surgical target selection for the treatment of tremors.